Окремі аспекти оцінки інвестиційної привабливості суб'єктів агробізнесу - Шиян, Наталія Іванівна (My University, 2021)
У статті визначено актуальність проблеми інвестиційної привабливості, проаналізовано теоретичні підходи до її розгляду. Особливу увагу приділена поширеним у практиці інвесторів підходам до визначення рівня інвестиційної привабливості країни, регіону, галузі, підприємства. Здійснено оцінку інвестиційної привабливості підприємств аграрної сфери економіки, зокрема підприємств, які спеціалізуються на виробництві продукції галузі рослинництва та які виробляють одночасно і продукцію рослинництва, і продукцію тваринництва. Результати дослідження свідчать, що на сучасному етапі розвитку аграрної сфери економіки України вищою є інвестиційна привабливість підприємств, які спеціалізуються на виробництві продукції рослинницької галузі, що створює проблему формування механізму підтримки розвитку тваринництва в них із боку держави, регіонів, органів місцевого самоврядування для підвищення рівня інвестиційної привабливості таких підприємств.

The article determines the relevance of the problem of investment attractiveness, analyzes the theoretical approaches to its consideration. Particular attention is paid to common in the practice of investors approaches to determining the level of investment attractiveness of the state, region, industry and enterprise. It was defined that the level of investment attractiveness is determined as an integral indicator with the addition of a set of indicators, which identify the characteristics of the sphere of activity, geographical location, strategic intentions, etc. Particular attention was paid to the index of investment attractiveness of Ukraine in accordance with the methodology of the European business organization. The factors and peculiarities of determining the investment attractiveness of the agrarian sphere were specified. The estimation of the investment attractiveness of enterprises of the agrarian sector of the economy with the use of data on the financial condition and efficiency of enterprises in the Kharkiv region in 2020, including enterprises that specialize in the production of crop production and those enterprises that simultaneously produce crop and livestock production was carried out. The results of the study indicate that at this stage of development of the agrarian sector of the economy of Ukraine the enterprises that specialize in the field of crop production have higher investment attractiveness, which creates a problem of forming a mechanism to support the development of animal husbandry in them by the state, regions and local governments to increase the investment attractiveness of such enterprises.
Particular aspects of assessing the investment attractiveness of agribusiness entities
Keywords: економіка; капіталовкладення; аграрні підприємства; фінансовий стан; ефективність; investment attractiveness; capital investments; agrarian enterprises; financial condition; efficiency